Handbook of Regional Growth and Development Theories 2019
DOI: 10.4337/9781788970020.00023
|View full text |Cite
|
Sign up to set email alerts
|

Regional development and knowledge

Abstract: This paper focuses on the concept of knowledge and examines models depicting and explaining the role of knowledge in regional development and provides an assessment of empirical studies of how knowledge affects growth and development in functional regions. For this paper it is crucial to understand those factors that make knowledge spatially sticky and knowledge-production capacity trapped. It is equally important to explain the conditions for knowledge flows and diffusion. The presentation also widens the vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 97 publications
1
3
0
2
Order By: Relevance
“…While the role of accessibility had been investigated for matters related to productivity and commuting (e.g., Johansson & Forslund, 1995;Ohlsson, 2002), in the 2000s only, this concept was used to improve our understanding of the importance of proximity to knowledge. The findings of this literature largely confirm an important role of proximity to R&D and human capital for patent production (e.g., Andersson & Ejermo, 2005;Gråsjö, 2006;Johansson & Karlsson, 2019). While this prior literature aimed at understanding the effects of proximity it did not focus on changes in accessibility, e.g., through changes in road travel times.…”
Section: Additionality Mechanismssupporting
confidence: 54%
“…While the role of accessibility had been investigated for matters related to productivity and commuting (e.g., Johansson & Forslund, 1995;Ohlsson, 2002), in the 2000s only, this concept was used to improve our understanding of the importance of proximity to knowledge. The findings of this literature largely confirm an important role of proximity to R&D and human capital for patent production (e.g., Andersson & Ejermo, 2005;Gråsjö, 2006;Johansson & Karlsson, 2019). While this prior literature aimed at understanding the effects of proximity it did not focus on changes in accessibility, e.g., through changes in road travel times.…”
Section: Additionality Mechanismssupporting
confidence: 54%
“…Knowledge is the newest form of capital asset and the ability to access and use knowledge can be measured as the access to knowledge-intensive labour that the region offers firms that locate to the region. This requires that the region is capable of attracting households that can supply this labour (Johansson & Karlsson, 2019). Maximizing value from Big Data value requires several factors, including the concentration of knowledge-based workers.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the production and use of industrial data in the United States' power-generation sector found that the location of industrial data activities (and the firms that emerge to participate in that production process) is highly sensitive to (Clark & Sudharsan, 2019): the underlying and existing sectoral geographies; connectivity (to internet-enabled devices and data transmission); and specialized labour markets and institutions and institutional capacity. Regions vary considerably in their resource endowments, infrastructure, institutional make-up and labour market characteristics (Bishop & Shilcof, 2017;Johansson & Karlsson, 2019). Many of these factors are either fixed or 'sticky', and they evolve slowly over time.…”
Section: Firms Regions and Absorption Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…A témakörrel foglalkozó irányzat kiemelkedő képviselői közül Romer (1986) a tudástőke, míg Lucas (1988) a tanulás és a humán tőke fontosságát emeli ki (Acs, Sanders 2021;Varga 2009). A regionális tudomány is átvette és továbbfejlesztette ezeket az alapvető eredményeket, kiemelve többek között a társadalmi tőke, a vállalkozókészség és az intézményi háttér (Johansson, Karlsson 2019;Stimson, Stough, Salazar 2009;Westlund, Larsson 2021), illetve -a nagyvárosok tudásbázisa kapcsán -a kreativitás és a tolerancia fontosságát (Florida, Mellander, Stolarick 2008;Lengyel, Ságvári 2009).…”
Section: Bevezetésunclassified